Strategies of Distribution Effectiveness of Special Physical Allocation Funds in The Field of Marine And Fisheries - Sharah Gita Kalila Lubis; Muhammad Firdaus; Tb. Nur Ahmad Maulana (Jurnal Manajemen & Agribisnis, 2018)
Indonesia still has tremendous opportunities to utilize and develop the potential of fisheries optimally. The government through DAK Marine and Fisheries Sector helps fund the physical development activities in the field of marine and fisheries to support fishery production. The effectiveness of DAK disbursement from the government to various regions becomes very important to accelerate the process of marine and fisheries development. The purposes of this research are as follows: (1) analyzing the constraints of DAK Marine and Fisheries Sector distribution; (2) analyzing the impact of DAK Marine and Fisheries Sector distribution; and (3) formulating the strategies needed to improve the effectiveness of DAK Marine and Fisheries Sector distribution. The processing techniques and data analysis in this research included data panel data regression analysis with Fixed Effect Model (FEM) method using Eviews 8 software and analysis of strategy formulation using Strengths - Weakness – Opportunities – Threats (SWOT) matrix. Based on the results of Regression, DAK Fishing Capture variables have no significant effects on Capture Fishery Production, while DAK Fishery Aquaculture variables have significant effects on Aquaculture Production. The results of formulation of alternative strategies using SWOT matrix exhibit the position point of IFE and EFE score points at the quadrant position III (Turn Around). The recommended strategy is the WO strategy i.e. to minimize the weaknesses to take advantages of opportunities.Keywords: DAK KP, effectiveness, FEM, SWOT Matrix, WO strategy